1987
DOI: 10.1055/s-2007-1003513
|View full text |Cite
|
Sign up to set email alerts
|

Binding Properties of Human Thrombospondin: Interaction with Mucopolysaccharides

Abstract: The interaction of human thrombospondin with mucopolysaccharides has been measured quantitatively. Binding of thrombospondin to heparin was examined utilizing an assay employing an 125I-labeled LMW heparin glycosaminoglycan (Mr = 8500). By this means, a class of binding sites was detected that bound approximately 2 moles of LMW heparin per mole of thrombospondin with a Kd of 2.4 nM. The binding stoichiometry of LMW heparin to thrombospondin was confirmed by fluorescence polarization experiments in which thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…11 TSP adsorbed at pH 4 showed a single class of binding sites that became saturated with 10 to 50 nM heparin, which represents weaker binding than has been estimated for the interaction of heparin to TSP in solution. 21 TSP adsorbed at pH 7.4 resulted in two classes of binding sites. Although the first binding site in the pH 7.4-adsorbed TSP had a stronger affinity than the single site in the pH 4-adsorbed TSP, it was only responsible for about 5% of the total binding.…”
Section: Effects Of the Heparin Oligosaccharides On The Immunofluoresmentioning
confidence: 99%
See 1 more Smart Citation
“…11 TSP adsorbed at pH 4 showed a single class of binding sites that became saturated with 10 to 50 nM heparin, which represents weaker binding than has been estimated for the interaction of heparin to TSP in solution. 21 TSP adsorbed at pH 7.4 resulted in two classes of binding sites. Although the first binding site in the pH 7.4-adsorbed TSP had a stronger affinity than the single site in the pH 4-adsorbed TSP, it was only responsible for about 5% of the total binding.…”
Section: Effects Of the Heparin Oligosaccharides On The Immunofluoresmentioning
confidence: 99%
“…6) of cellular interactions with TSP to explain these observations. The solution studies of Slayter et al 21 showed that three heparin molecules bind tightly per TSP trimers. In our hands, the monomelic amino-terminal heparin-binding fragment purified after thrombin digestion did not bind specifically to cell layers (Sun X, DF Mosher: Unpublished observations).…”
Section: Fig 5 Effects Of Heparin Oligosaccharides On the Immunoflumentioning
confidence: 99%
“…It has been suggested that TSP may have an important role in many physiological and pathological processes like cell-matrix communication, wound healing, hemostasis, morphogenesis and angiogenesis (Jaffe et al 1983;Silverstein et al 1984;Tar-aboletti et al 1990) through its interaction with a various kind of molecules such as fibronectin, collagen, laminin, proteoglycan, fibrinogen and plasminogen (Lahav et al 1984;Mumby et al 1984;Slayter et al 1987).…”
mentioning
confidence: 99%